2002
DOI: 10.1046/j.1439-0450.2002.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Porcine Circovirus Type 2 (PCV‐2) Infection of Pigs in the Czech Republic by Semi‐Nested PCR

Abstract: Three oligonucleotide primers for semi-nested polymerase chain reaction (PCR) were designed according to already published sequences of porcine circovirus types 1 (PCV-1) and 2 (PCV-2) isolates. These primers were used to detect PCV-2 DNA. A positive amplification reaction was visualized from a DNA suspension containing as few as 10 copies of virus DNA. In total. 77 samples of inguinal lymph nodes and nasal swabs from pigs in the Czech Republic were used to detect the virus. Thirty-seven of them were positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Porcine circovirus type 2 (PCV2) as an etiological agent of porcine circovirus diseases (PCVDs) was firstly identified in the 1990s in Canada [ 1 ], and was later detected and characterized in USA and Europe [ 2 , 3 ]. In the Czech Republic and Slovakia PCV2 in pigs was confirmed and genetically typed a few years later [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Porcine circovirus type 2 (PCV2) as an etiological agent of porcine circovirus diseases (PCVDs) was firstly identified in the 1990s in Canada [ 1 ], and was later detected and characterized in USA and Europe [ 2 , 3 ]. In the Czech Republic and Slovakia PCV2 in pigs was confirmed and genetically typed a few years later [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it was shown that this virus can be transmitted vertically Ladekjaer-Mikkelson et al, 2001;O'Connor et al, 2001;Sanchez et al, 2001] there is a common view that this virus is associated with severe pathology in newborn piglets, and its vertical transmission is a rare event. Three facts call special attention in assessment of the infection risk associated with xenotransplantation: ubiquity of the PCV type 2 virus [Labarque et al, 2000;Trujano et al, 2001;Celera and Carasova, 2002;Kim et al, 2002;Liu, 2002;Wattrang et al, 2002;Garka- [Hattermann, 2002, own unpublished data], and in experimental mice in vivo [Kiupel, 2001]. All these facts need more intensive study.…”
Section: Discussionmentioning
confidence: 99%
“…Three factors must be considered when assessing the infectious risk of PCV2 associated with xenotransplantation: (1) the ubiquity of the PCV type 2 virus (Celera & Carasova, 2002;Garkavenko et al, 2005;Kim et al, 2002;Labarque, Nauwynck, Mesu, & Pesaert, 2000;Trujano, Iglesias, Segales, & Palacios, 2001;Wattrang et al, 2002); (2) the potential that the virus might be transmitted vertically without showing any sign of abnormality and (3) transmission of the virus occurs in human cells in vitro (Hattermann, 2002, unpublished data), and in experimental mice in vivo (Kiupel et al, 2001). Despite evidence that caesarean section and barrier rearing techniques are effective in excluding PCV and PLHV from pig populations, these interventions do not guarantee the exclusion of all viruses from a pig herd (Tucker et al, 2003).…”
Section: Determining Infections Relevant To Xenotransplantation In Nzmentioning
confidence: 99%